Hope flames - Burton, Jaci (Burton, Jaci. Hope novels., 2014)
Thirty-two and finally setting up her veterinary practice in the town she once called home, Emma Burnett is on her own and loving it. Independent and driven, she's not letting any man get in the way of her dreams. Not again. That's fine with Luke McCormack. Divorced and hardly lacking in female company when he needs it, he's devoted to the only faithful companion in his life, his police dog. Still, there's something about Emma he cannot shake. When a series of local break- ins leaves Emma vulnerable, she seeks help from the first man to spark her desire in years. And now they're giving each other something they thought they'd lost forever, hope.